(untitled) (Brazilian Journal of Radiation Sciences, 2017)
After the Earthquake in Bam in December 26, 2003, a team was dispatched to this area to monitor the relationship between Variation in the Radon (222Rn) concentration and the magnitude of aftershocks. Meteorological parameters such as air pressure, temperature and humidity were measured. Radon concentration at depth of 90 cm of soil was also measured using AlphaGuard (Model 2000PRO) in 10 minutes periods. The measurement site was near the fault location and the radon concentration was systemically measured for a period of three months. A correlation between radon concentration and the available aftershocks data is discussed. More than 150 small to moderate aftershocks with a magnitude ranging from M=2.1 to 6.5 in scale of Richter occurred in the region during the period of this study at the various distances (below 20 km of epicenter) from the radon monitoring sites. When the magnitude of aftershocks increased, variation of radon concentration could be seen more clearly.